THE FORMATION OF IDEOLOGICAL AND IDEOLOGICAL IMMUNITY IS AN IMPORTANT CONDITION FOR THE FORMATION OF A HARMONIOUS PERSONALITY - Nadira Nazarkulovna Eshmanova (Galaxy International Interdisciplinary Research Journal, 2022)
The article outlines the foundations of the formation of ideological and ideological immunity-the foundations of the formation of a harmonious personality, its special place in the historical development of mankind, the essence of ideological and ideological struggle, the conflict of ideological interests.